Pemerolehan Bahasa Tataran Sintaksis Anak Usia 4 Tahun (Studi Kasus Amira Nadhifa Hidayah) - Adila, Nova Putri (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
Humans in their lives acquire language from their environment and use language. Humans use language as a means of communication. Syntax language acquisition is obtained by children gradually, from small things first and then moving on to bigger things, meaning that children master words, phrases, clauses and then sentences. A child will convey a message or desire in the form of news sentences, questions and commands. This thesis has the title of language acquisition at the syntactic level of children aged 4 years (case study of Amira Nadhifa Hidayah). The problems studied in this thesis are: (1) How is the formation of declarative sentences in children aged 4 years (case study amira Nadhifa Hidayah)? (2) How is the formation of imperative sentences in children aged 4 years (case study Amira Nadhifa Hidayah)? (3) How is the formation of interrogative sentences in children aged 4 years (case study Amira Nadhifa Hidayah)? The purpose of this study is to describe, analyze and interpret in detail and systematically in declarative, interrogative, imperative sentences that occur in children aged 4 years. The theory that the author uses in discussing this problem is the theory of Chaer (2009:187-199) and Dardjowijojo (2000:199-202). The data sources of this study were all sentences uttered by a 4 year old child (case study of Amira Nadhifa Hidayah) while the object data were declarative, interrogative, and imperative sentences in a 4 year old child in the language acquisition process. The method used is a descriptive method with data collection using listening techniques, recording techniques, fishing techniques, note-taking techniques, matching techniques. The results of this study are that there are 66 data from declarative sentences uttered by children aged 4 years (case study Amira Nadhifa Hidayah), 45 data from interrogative sentences uttered by Amira Nadhifa Hidayah and 17 data from imperative sentences uttered by Amira Nadhifa Hidayah.